HOW ISRAEL IS USING ILLEGAL MEANS TO DEPRIVE PALESTINIANS OF THEIR HISTORICAL LEGITIMATE RIGHT TO RECLAIM THEIR OCCUPIED HOMELAND: HISTORICAL AND LEGAL EXPLORATORY - Mohammed Houmine (Journal Of Social And Political Science, 2026)
Events related to the Palestinian question are accelerating. Before the development of the situation in the United Nations arena, which led to the establishment of an independent Palestinian state, a plethora of solutions were proposed. These included the annexation of the Palestinian territories to the Jordanian confederation and the granting of autonomy to the residential groups. However, certain individuals have proposed highly unconventional and impractical proposals, such as the acquisition of the Gaza Strip for developing it into a tourist resort, the expulsion of its current inhabitants to Egypt and Jordan, and the annexation of the West Bank to Israel. This research aims to show how Israel has deprived Palestinians of their right to self-determination. A historic and legal exploratory approach was used to examine and analyse the various data available on this topic. The findings revealed all the irregular measures taken by the Zionists to prevent the Palestinians from achieving an independent homeland. Finally, the study recommends that the international legal order assume its historic responsibility to defend the legality of the fundamental Palestinian rights and secure peace in the Middle East, in accordance with international law, international humanitarian law, and international covenants.